The Trinity : An Introduction to Catholic Doctrine on the Triune God - Emery, Gilles (Book collections on Project MUSE., 2012)
Representing the highest quality of scholarship, Gilles Emery offers a much-anticipated introduction to Catholic doctrine on the Trinity. His extensive research combined with lucid prose provides readers a resource to better understand the foundations of Trinitarian reflection. The book is addressed to all who wish to benefit from an initiation to Trinitarian doctrine.